Proceedings of the Fifteenth ACM Conference on Economics and Computation 2014
DOI: 10.1145/2600057.2602845
|View full text |Cite
|
Sign up to set email alerts
|

Bounds for the query complexity of approximate equilibria

Abstract: We analyze the number of payoff queries needed to compute approximate equilibria of multi-player games. We find that query complexity is an effective tool for distinguishing the computational difficulty of alternative solution concepts, and we develop new techniques for upper-and lower bounding the query complexity. For binary-choice games, we show logarithmic upper and lower bounds on the query complexity of approximate correlated equilibrium. For well-supported approximate correlated equilibrium (a restricti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 28 publications
(27 reference statements)
0
32
0
Order By: Relevance
“…The query complexity of equilibria of n-player games -a setting where payoff functions are exponentially-large -was analyzed in [4,8,21,22]. [22] showed that exponentially many deterministic queries are required to find a 1 2 -approximate correlated equilibrium (CE) and that any randomized algorithm that finds an exact CE needs 2 Ω(n) expected cost.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The query complexity of equilibria of n-player games -a setting where payoff functions are exponentially-large -was analyzed in [4,8,21,22]. [22] showed that exponentially many deterministic queries are required to find a 1 2 -approximate correlated equilibrium (CE) and that any randomized algorithm that finds an exact CE needs 2 Ω(n) expected cost.…”
Section: Related Workmentioning
confidence: 99%
“…Notice that lower bounds on correlated equilibria automatically apply to Nash equilibria. [21] investigated in more detail the randomized query complexity of ǫ-CE and of the more demanding ǫ-wellsupported CE. [4] proved an exponential-in-n randomized lower bound for finding an ǫ-WSNE in n-player, k-strategy games, for constant k = 10 4 and ǫ = 10 −8 .…”
Section: Related Workmentioning
confidence: 99%
“…There are two results that we will use for this setting. Goldberg and Roth [14] have given a randomized algorithm that, with high probability, finds an -NE of a zerosum game using O( n•log n…”
Section: Lemma 1 ([13]mentioning
confidence: 99%
“…Hence, we obtain a randomized expectedpolynomial-time algorithm that uses poly-logarithmic communication and finds a The algorithm can also be used to beat the best known bound in the query complexity setting. It has already been shown by Goldberg and Roth [14] that an -NE of a zerosum game can be found by a randomized algorithm that uses O( n log n…”
Section: Introductionmentioning
confidence: 99%
“…For randomised algorithms, query complexity is exponential for well-supported approximate equilibria [3], which has since been strengthened to any ε-Nash equilibria [5]. With randomised algorithms, the query complexity of approximate correlated equilibrium is (log n) for any positive ε [10].…”
Section: Introductionmentioning
confidence: 99%